Examining the Legacy of the 2008 Summer Olympics and 2022 Winter Olympics on Mass Sports Participation in China - Wu, Yiran (Πανεπιστήμιο Πελοποννήσου, 2025)
This study investigates the ongoing and potential impacts of the 2008 Beijing Summer Olympics and the 2022 Beijing Winter Olympics on sports participation in China through a mixed-method approach. By systematically reviewing and analyzing key policy documents, including the National Fitness Plan, Health China 2030 Planning Outline, and various policies, the study explores the theoretical underpinnings and policy evolution associated with the Olympics in China. The quantitative analysis employs data from national sports industry reports, facility surveys, and nationwide fitness studies conducted between 1995 and 2023. This analysis reveals significant trends in the increase in sports facilities and a substantial rise in national fitness participation rates, largely attributed to the strategic use of Olympic infrastructure and the implementation of related policies. The findings indicate that both Olympic events served as crucial catalysts for expanding China's sports industry and enhancing public fitness engagement. Additionally, the study finds that these events have left a legacy by embedding a culture of physical fitness into everyday life, significantly altering public attitudes toward sports and health. The study highlights the importance of sustained government support to ensure the ongoing benefits of these developments while also addressing regional disparities in access to sports facilities and participation opportunities. This research enriches the understanding of the Olympic legacy in the context of national sports development, providing valuable insights for future policy-making. It underscores the importance of sustained governmental support and strategic planning in leveraging large-scale sporting events to achieve sustained public health and social development goals.
Keywords: Αθλητισμός - Μάρκετινγκ - Κίνα; Αναψυχή - Διοίκηση και οργάνωση - Κίνα; Αθλητικές εγκαταστάσεις - Διοίκηση και οργάνωση - Κίνα; Φυσική κατάσταση; Θερινοί Ολυμπιακοί Αγώνες - Κίνα; Χειμερινοί Ολυμπιακοί Αγώνες - Κίνα; Sports - Marketing - China; Recreation - Management - China; Sports facilities - Management - China; Physical fitness; Summer Olympics - China; Winter Olympics - China; Olympic legacy; sports participation; sports industry; China